European Symposium on Computer Aided Process Engineering-12 : 35th European symposium of the Working Party on Computer Aided Process Engineering : ESCAPE-12, 26-29 May, 2002, the Hague, the Netherlands /: 35th European symposium of the Working Party on Computer Aided Process Engineering : ESCAPE-12, 26-29 May, 2002, the Hague, the Netherlands. (2002) - Unknown
No abstract available